2021
DOI: 10.1016/j.ajem.2020.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital management of acute respiratory distress in suspected COVID-19 patients

Abstract: Background In December 2019, coronavirus disease (COVID-19) emerged in China and became a world-wide pandemic in March 2020. Emergency services and intensive care units (ICUs) were faced with a novel disease with unknown clinical characteristics and presentations. Acute respiratory distress (ARD) was often the chief complaint for an EMS call. This retrospective study evaluated prehospital ARD management and identified factors associated with the need of prehospital mechanical ventilation (PMV) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“… Clinical Assessment 38 Jouffroy et. al 50 Prehospital management of acute respiratory distress in suspected COVID-19 patients Cohort EMS and Hospital Patient Care Records Paris, FR ● 15% of 256 patients with COVID-19 symptoms died at the scene but there was a low prevalence of prior cardiovascular risk factors. ● Out of the 185 patients analyzed 44% were transported via BLS and 42% received non- invasive ventilation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Clinical Assessment 38 Jouffroy et. al 50 Prehospital management of acute respiratory distress in suspected COVID-19 patients Cohort EMS and Hospital Patient Care Records Paris, FR ● 15% of 256 patients with COVID-19 symptoms died at the scene but there was a low prevalence of prior cardiovascular risk factors. ● Out of the 185 patients analyzed 44% were transported via BLS and 42% received non- invasive ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that of the suspected COVID-19 patients who were assessed by EMS personnel, 42% of BLS cases and 52% of ALS cases provided non-invasive ventilation, however, prehospital intubation was significantly less common as it was only present in 18% of ALS cases. 50 , Jouffroy et al report that of all COVID−19 suspected patients, 53.4% showed signs of respiratory distress. Most of these patients presented with respiratory rates of approximately 30/min and oxygen saturations of 72%.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that it is critical to provide sufficient respiratory support in the prehospital setting. It was found that of the suspected COVID-19 patients who were assessed by EMS personnel, 42% of BLS cases and 52% of ALS cases provided non-invasive ventilation, however, prehospital intubation was significantly less common as it was only present in 18% of ALS cases (50) . Jouffroy et al report that of all COVID-19 suspected patients, 53.4% showed signs of respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…Similar scenarios of trainings could initiate a synergy effect in common disaster response (Rojek andSmith, 2007, Laufs andWaseem, 2020;Beerens et al, 2020). The obvious pandemic co-operator to fire rescue service is healthcare service which states a core emergency foundation in pandemic and needs operational support from other emergency services, public administration etc., (Jouffroy et al, 2020). It finds its justification in preparing emergency infrastructure to disasters (Ortiz-Barrios et al, 2020) and fighting barriers in interorganizational disaster response (Berchtold et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…High cooperation potential with police should be noticed (Laufs and Waseem, 2020). Just like with healthcare service, in the context of preliminary identification of infected people (Jouffroy et al, 2020), important in epidemic risk reduction (Alcantara-Ayala et al, 2020). Emergency sheltering can be supported by fire rescue service as well.…”
Section: Literature Reviewmentioning
confidence: 99%